Pengaruh Variasi Bukaan Katup terhadap Kinerja Sistem pada Konfigurasi Pompa Seri dan Paralel - David Jomantes Munthe; Jimy Lingga; Jufrizal Jufrizal; Muhammad Idris (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Centrifugal pumps are widely used in industry and civil engineering to move fluids by increasing pressure efficiently. This study analyzes the effect of valve opening variations on series and parallel pump configurations simultaneously using a laboratory experiment method with two repetitions. The results show that parallel pump configurations are generally more efficient than series, especially at 50% and 25% valve openings. The maximum efficiency is achieved at 75% valve opening with a value of around 33% for both configurations. Valve opening settings and pump configuration selection are very important to improve the performance and efficiency of pressure piping systems. It is recommended for small industries to use parallel pump configurations with optimal valve opening operations of around 75% for energy efficiency and cost savings. Developing an automatic valve opening control system is also recommended to maximize efficiency, extend equipment life, and optimize fluid distribution.